Review of Clinical Evidence over 10 Years on Prevention and Treatment of a Film-Forming Medical Device Containing Photolyase in the Management of Field Cancerization in Actinic Keratosis - Susana Puig; Corinne Granger; Aurora Garre; Carles Trullàs; Onofre Sanmartin; Giuseppe Argenziano (Adis, Springer Healthcare, 2019)
Abstract Actinic keratosis (AK) is a common pathology that afflicts sun-exposed areas of the skin. It predominantly affects older and fair-skinned individuals suggesting an accumulative damage attributable to chronic sun exposure. The prevalence of AK has risen in the past decades and is expected to continue to rise. Apart from visible hyperkeratotic, hyperplastic lesions, AK is also associated with the presence of subclinical lesions adjacent to tumor tissue, which has led to the use of the concept "cancerization field". Although lesion- and field-targeting treatments are currently available, many are associated with local side effects and recurrence of new lesions. This review provides information on AK pathophysiology and treatment options and summarizes the available clinical evidence supporting the use of Eryfotona AK-NMSC, a film-forming medical device with SPF 100+ containing the DNA repair enzyme photolyase, for managing AK, based on the analysis of the results of 228 patients treated with the product. Funding ISDIN funded the Article Processing Charges.